Mid-Miocene magmatism in the Owyhee Mountains, ID: origin and petrogenesis of volcanic rocks in the Silver City district - Hasten, Zachary Eugene Levi (Kansas State University, 2012)
Previous studies of the northern Great Basin have indicated that mid-Miocene epithermal gold and silver ore deposits distributed regionally are temporally related to the magmatic activity associated with the onset of widespread extension and the Yellowstone hotspot (Saunders and Crowe, 1996; Kamenov et al., 2007). This study is focused on the volcanic rocks and ore deposits from the Silver City district (SCD), ID to address the petrogenesis and magmatic evolution that was influential in forming local precious metal deposits. The goal is to understand the tectonomagmatic conditions that contributed to the petrogenesis of the volcanic suite in the Silver City district, which can be used to provide details on the relationship between coeval mid- Miocene magmatism and mineralization across the northern Great Basin and Oregon Plateau. In order to better constrain the magmatic evolution of the SCD and potential sources of the precious metals, we have undertaken detailed sampling of local crust and mid-Miocene volcanic units to constrain their physical, geochemical, isotopic, and geochronological characteristics, as well as provide constraints on the petrogenesis of the mid-Miocene volcanic package. Prior studies of the local volcanism have yielded K-Ar and [superscript]40Ar/[superscript]39Ar ages of ~16.6 to 14 Ma (Bonnichsen, 1983), while others have dated adularia from one SCD mineral vein and obtained [superscript]40Ar/[superscript]39Ar ages of between 15.6 and 16.3 Ma (Hames et al., 2009; and Aseto et al., 2011). Field observations are consistent with earlier work (Lindgren, 1900; Asher, 1968; Pansze, 1975; Halsor et al., 1988; Bonnichsen and Godchaux, 2006; Camp and Ross, 2009) and reveal a sequence of basalt consisting of regionally prevalent Steens Basalt that pre-dated precious metal mineralization. Some of the basalt appears to have been erupted locally, based on the presence of mafic dikes and thick pyroclastic deposits similar to other regional mid-Miocene magmatic systems. Stratigraphically overlying this lower basalt suite is a complex package of rhyolite flows and domes, thin silicic pyroclastic units, additional basaltic lava flows, intermediate lava flows, and mafic/silicic shallow intrusives. Geochemical analysis indicates that the basaltic and basaltic andesite lava flows are locally erupted flows of Steens Basalt while the intermediate and silicic volcanism in SCD can be classified into nine distinct units including two andesites, one dacite, four rhyolites and two rhyolite tuffaceous units. Geochemical modeling suggest that the intermediate and silicic magmas were formed by a combination of open system processes, including low pressure partial melting and assimilation of mid to upper crustal granitoid basement rock, and magma mixing between silicic and basaltic endmembers. The formation of silicic volcanism in the SCD is similar to other regional mid-Miocene silicic volcanic systems (e.g. Santa Rosa-Calico volcanic field and Jarbidge Rhyolite). Based on new [superscript]40Ar/[superscript]39Ar geochronology of both volcanic units and epithermally emplaced mineralization, SCD volcanism appears to have erupted over a relatively short amount of time that overlaps with local epithermal Au-Ag mineralization.
Keywords: Basalt; Rhyolite; Yellowstone; Owyhee Mountains; Epithermal deposits; Magma mixing; Geochemistry (0996); Geology (0372); Petrology (0584)